Best practice weed detection on Australian farms. (November 2015) - Coleman, Michael J.; Sindel, Brian M.; Reeve, Ian J.; Thompson, Lyndal-Joy
Highlights: We surveyed Australian rural landholders and weeds officers on best practice weed detection. Landholders regularly searched for weeds, but were often reluctant to report new outbreaks. Weeds officers are important in providing detection and identification advice to landholders. Non-professional landholders were considered to be relatively poor weed managers. Extension activity must target these landholders and encourage cooperation with weeds officers. Abstract: Agricultural weeds impose a significant cost on Australian farmers and consumers. The first step in controlling weeds on-farm is successful detection. The sooner new weed invasions are detected, the more effective management strategies will be. This research sought to collate 'best practice' principles for weed detection by surveying those individuals who play a part in weed detection and control on Australian farms – landholders and weeds officers. We found that landholders regularly checked their property for weeds, but were often reluctant to report new weed outbreaks. Weeds officers had an important role in improving weed detection on-farm, by providing advice and information to landholders, and encouraging more landholders to report weed outbreaks. While there were many similarities in the best practice approaches used by landholders and weeds officers to inspect land for weeds, weeds officers had access to a range of resources that made it considerably easier to identify a new weed species. It was also found that there were particular segments within the broad landholder group (such as non-professional landholders), who were considered relatively poor weed managers. Extension work in this area therefore needs to encourage close cooperation with weeds officers, targeting specific landholder groups for extension and access to expert advice, while continuing to educate all landholders in the areas of weed identification, and the best practice detection and control techniques used by weeds officers.